Assessing the Quality of Teleconsultations in a Store-And-Forward Telemedicine Network - Wootton, Richard; Liu, Joanne; Bonnardot, Laurent (Frontiers in Public Health, 2014)
Store-and-forward telemedicine in resource-limited settings is becoming a relatively mature activity. However, there are few published reports about quality measurement in telemedicine, except in image-based specialties, and they mainly relate to high- and middle-income countries. In 2010, Médecins Sans Frontières (MSF) began to use a store-and-forward telemedicine network to assist its field staff in obtaining specialist advice. To date, more than 1000 cases have been managed with the support of telemedicine, from a total of 40 different countries. We propose a method for assessing the overall quality of the teleconsultations provided in a store-and-forward telemedicine network. The assessment is performed at regular intervals by a panel of observers, who – independently – respond to a questionnaire relating to a randomly chosen past case. The answers to the questionnaire allow two different dimensions of quality to be assessed: the quality of the process itself and the outcome, defined as the value of the response to three of the four parties concerned, i.e., the patient, the referring doctor, and the organization. It is not practicable to estimate the value to society by this technique. The feasibility of the method was demonstrated by using it in the MSF telemedicine network, where process quality scores, and user-value scores, appeared to be stable over a 9-month trial period. This was confirmed by plotting the cusum of a portmanteau statistic (the sum of the four scores) over the study period. The proposed quality-assessment method appears feasible in practice, and will form one element of a quality assurance program for MSF’s telemedicine network in future. The method is a generally applicable one, which can be used in many forms of medical interaction.